Uses of turmeric in dentistry: An update - Chaturvedi T (Wolters Kluwer Medknow Publications, 2009)
Turmeric has been used for thousands of years as a dye, a flavoring, and a medicinal herb. In India, it has been used traditionally as a remedy for stomach and liver ailments, as well as topically to heal sores. Ancient Indian medicine has touted turmeric as an herb with the ability to provide glow and luster to the skin as well as vigor and vitality to the entire body. Since turmeric has antimicrobial, antioxidant, astringent, and other useful properties, it is quite useful in Dentistry also. The objective of this article is to highlight various uses of turmeric in the dental field along with its use in medical problems.